A novel human monoclonal antibody specific to the A33 glycoprotein recognizes colorectal cancer and inhibits metastasis - Patrizia Murer; Louis Plüss; Dario Neri (Taylor & Francis Group, 2020)
Colorectal cancer represents the second most common cause of cancer-related death. The human A33 transmembrane glycoprotein is a validated tumor-associated antigen, expressed in 95% of primary and metastatic colorectal cancers. Using phage display technology, we generated a human monoclonal antibody (termed A2) specific to human A33 and we compared its epitope and performance to those of previously described clinical-stage anti-human A33 antibodies. All antibodies recognized a similar immunodominant epitope, located in the V-domain of A33, as revealed by SPOT analysis. The A2 antibody homogenously stained samples of poorly, moderately, and well differentiated colon adenocarcinomas. All antibodies also exhibited an intense staining of healthy human colon sections. The A2 antibody, reformatted in murine IgG2a format, preferentially localized to A33-transfected CT26 murine colon adenocarcinomas in immunocompetent mice with a homogenous distribution within the tumor mass, while other antibodies exhibited a patchy uptake in neoplastic lesions. A2 efficiently induced killing of A33-expressing cells through antibody-dependent cell-mediated cytotoxicity in vitro and was able to inhibit the growth of A33-positive murine CT26 and C51 lung metastases in vivo. Anti-A33 antibodies may thus represent useful vehicles for the selective delivery of bioactive payloads to colorectal cancer, or may be used in IgG format in a setting of minimal residual disease.